Multi-scale tomographic analysis of polymeric foams: A detailed study of the cellular structure. (December 2018) - Pérez-Tamarit, S.; Solórzano, E.; Hilger, A.; Manke, I.; Rodríguez-Pérez, M.A.
Graphical abstract: Highlights: A multi-scale tomographic approach was used to study the structure of polymeric foams. Gaseous phase features were examined using conventional lab-scale X-ray tomography. Solid phase parameters were analysed by means of synchrotron X-ray tomography. A novel analysis method to separate the solid phase in struts and walls was developed. Abstract: This manuscript presents a detailed characterization of the cellular structure of two types of polymeric foams by non-destructive multi-scale X-ray computed micro-tomography. This comparative study is conducted in two different polymeric materials –rigid polyurethane foams and cross-linked low density polyethylene foams-. Based on this technique and using 3D image analysis, conventional descriptors of the foams gaseous phase (cell size distribution, mean cell size and anisotropy ratio) are characterized at a standard voxel size of 5 µm. Complementarily, 0.4 µm voxel size synchrotron X-ray tomography data sets have been used to characterize, using a new image analysis approach, features of the solid phase of the foams (fraction of mass in the struts and thickness of the different entities of the solid architecture: struts and walls). The presented methodology, based on multi-scale tomographic analysis, allows obtaining a better understanding of the connection between foaming process and cellular structure and is important to gain knowledge on the structure-properties relationships for these materials.